1991
DOI: 10.1001/archsurg.1991.01410250080013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Granulocyte-Macrophage Colony-Stimulating Factor in Burn Patients

Abstract: We studied the effects of granulocyte-macrophage colonygranulocyte dysfunction may contribute significantly to the stimulating factor In burn patients. Serial measurements of granmarked predisposition to infection. ' ulocyte oxidative function were obtained In treated patients and Granulocyte-macrophage colony-stimulating factor (GMin a group of controls matched for age and total bum size. The CSF) is a lymphokine that was first described nearly 20 years administration of 4granulocyte-macrophage colony-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…This approach has been proposed previously. Specifically, treatment with granulocyte colony-stimulating factor or granulocyte-macrophage colony-stimulating factor (GM-CSF) after burn injury has been shown to have positive effects on survival and immune cell function (10,17), including improved T-cell proliferation and IL-2 production in a rat burn model (29).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been proposed previously. Specifically, treatment with granulocyte colony-stimulating factor or granulocyte-macrophage colony-stimulating factor (GM-CSF) after burn injury has been shown to have positive effects on survival and immune cell function (10,17), including improved T-cell proliferation and IL-2 production in a rat burn model (29).…”
Section: Discussionmentioning
confidence: 99%
“…Both G-CSF and GM-CSF improved immune function in animal models of burn-associated sepsis (17,18). Treatment of burn patients with GM-CSF improved neutrophil activities in vitro, but effects on the incidence of infections or mortality were not reported (19). It is likely that the most widely effective therapies will be those that impact numerous effector cells, which may require combinatorial therapies.…”
mentioning
confidence: 99%
“…They found external used rhGM-CSF can inhibit the wound healling delay caused by bacteria infection. Cioffi [6] et al use rhGM-CSF intravenously for burn patients in an randomly-controlled observation. They found that after 4 day's administration white blood count in treatment group was significant higher than that in control group, and blood bacterial culture presented negative in treatment group.…”
Section: Discussionmentioning
confidence: 99%